PHYSICAL ACTIVITY ACROSS THE WHOLE-OF-DAY AND VASCULAR STRUCTURE AND FUNCTION: THE PARIS PROSPECTIVE STUDY III. (June 2018) - Climie, R.; Boutouyrie, P.; Chaussade, E.; Plichart, M.; Offredo, L.; Guibout, C.; Thomas, F.; Pannier, B.; Laurent, S.; Jouven, X.; Empana, J.P.
Abstract : Objective: Habitual physical activity (PA) may be beneficial for reducing risk related to cardiovascular (CV) disease by attenuating age-related changes in vascular structure and function. Most previous studies have focused on recreational PA and individual markers of vascular health. We aimed to extend this work by investigating habitual physical activity across the whole-of-day (at work, during leisure and sport time) and several markers of structural and functional vascular health. Design and method: In 9277 adults aged 50 to 75 years from The Paris Prospective Study III, resting carotid artery structure (cross sectional area and external and internal diameters) and function (stiffness, Youngs elastic modulus, distensibility and cross sectional compliance) were determined via high-precision echotracking. Whole-of-day PA was self-reported using the validated Baecke score as overall PA (OPA), work PA (WPA), leisure time PA (LPA) and sport PA (SPA). The associations between PA (exposure) and vascular parameters (outcomes) were quantified using multivariate linear regression adjusted for age, sex, body mass index, total cholesterol and antihypertensive medication use. Results: OPA was associated with lower stiffness (B = −0.03 (0.009), p = 0.01) and Youngs (B = −3.59 (1.57), p = 0.02) and borderline higher distensibility (B = 0.12 (0.05), p = 0.05) and compliance (B = 0.003 (0.002), p = 0.07). WPA was significantly related to elevated stiffness and Youngs and decreased compliance (p < 0.05 for all) and borderline decreased distensibilty (p = 0.11); these association were mediated by how physically demanding the work was (i.e. lifting heavy loads). LPA and SPA were significantly associated with lower stiffness and Youngs and higher distensibility and compliance (p < 0.05 for all, the magnitude of the effect being greater for SPA). Light-moderate intensity SPA, but not high intensity, was associated with more favorable functional parameters (p < 0.05 for all) and lower wall cross sectional area (B = −0.12 (0.07), p < 0.01), external artery diameter (B = −28.4 (13.9), p = 0.04) and borderline lower internal diameter (B = −27.2 (14.9), p = 0.07). Conclusions: PA during leisure time and sport is associated with favorable vascular function and to a lesser degree, structure. However, PA at work (i.e. physically demanding work) is related to adverse changes in vascular function.